2008
DOI: 10.1007/s00114-008-0499-0
|View full text |Cite
|
Sign up to set email alerts
|

The last polar dinosaurs: high diversity of latest Cretaceous arctic dinosaurs in Russia

Abstract: A latest Cretaceous (68 to 65 million years ago) vertebrate microfossil assemblage discovered at Kakanaut in northeastern Russia reveals that dinosaurs were still highly diversified in Arctic regions just before the Cretaceous-Tertiary mass extinction event. Dinosaur eggshell fragments, belonging to hadrosaurids and non-avian theropods, indicate that at least several latest Cretaceous dinosaur taxa could reproduce in polar region and were probably year-round residents of high latitudes. Palaeobotanical data su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 24 publications
0
45
0
Order By: Relevance
“…Conifers are assigned to the Taxodiaceae, Cupressaceae and Pinacea. Godefroit et al (2008) report that of the ten gymnosperm taxa identified four are regarded as evergreen, but these are not specified or illustrated. This composition indicates warmer conditions than those of both the Kogosukruk and Cantwell Floras.…”
Section: And 4) and The Late Maastrichtian-danianmentioning
confidence: 95%
See 1 more Smart Citation
“…Conifers are assigned to the Taxodiaceae, Cupressaceae and Pinacea. Godefroit et al (2008) report that of the ten gymnosperm taxa identified four are regarded as evergreen, but these are not specified or illustrated. This composition indicates warmer conditions than those of both the Kogosukruk and Cantwell Floras.…”
Section: And 4) and The Late Maastrichtian-danianmentioning
confidence: 95%
“…Dinosaurs are also known from the Cretaceous of Northeastern Russia (Godefroit et al, 2008;Nessov, 1995Nessov, , 1997Nessov and Golovneva, 1990) and in addition to isolated bones and teeth, dinosaur eggshell fragments have been recovered from the late Maastrichtian Kakanaut Formation, Pekulnei Lake (Godefroit et al, 2008). As in Northern Alaska the hadrosaurs are well represented and their remains dominate Maastrichtian skeletal assemblages in Northeastern Russia (Godefroit et al, 2004).…”
Section: The Late Cretaceous Arctic Faunamentioning
confidence: 96%
“…Similarly, abundance measures are also potentially distorted by taphonomic and palaeoenvironmental heterogeneity over time 21 . Finally, understanding the global picture of Late Cretaceous dinosaur evolution may be complicated by a traditional focus on the North American record 22 , particularly the abundance and distribution of dinosaurs within a single formation (Hell Creek Formation). This is understandable, as the Hell Creek is one of the few units that globally preserves a dinosaurdominated ecosystem and a precisely located Cretaceous-Palaeogene boundary [4][5][6][7][8] , but may be only partially informative, if there were region-specific trends in biodiversity.…”
mentioning
confidence: 99%
“…At sea level, conditions were likely ice-free during this period, although in the nearby mountains permanent ice packs may have been able to form. Climate equability may have been greater during this time due to the increased sea level and large regions of flooded inland areas, with nearby waters providing a moderating effect and preventing typical continental climate systems from forming (Wolfe and Upchurch 1987), and may in part explain the existence of diverse nonmarine reptilian faunas in the Arctic, but the widespread distribution of dinosaurs throughout the Arctic continues to present intriguing palaeobiological questions (Brouwers et al 1987;Paul 1988, Tarduno et al 1998Rich et al 2002;Buffetaut 2004;Godefroit et al 2009). …”
Section: Review Of Mesozoic Terrestrial Vertebrates From the Canadianmentioning
confidence: 97%
“…The high palaeolatitude of these localities implies extreme seasonal variation in sunlight and vegetation (Spicer and Parrish 1990). The implications of these conditions on dinosaur palaeobiology, distributions, and extinction are poorly understood and controversial (Brouwers et al 1987;Paul 1988;Rich et al 2002;Buffetaut 2004;Godefroit et al 2009). Furthermore, there are few records of Mesozoic terrestrial fossils reported between these localities and central Alberta, where dinosaur faunas are well documented Arbour and Graves 2008;Currie et al 2008;Fanti and Miyashita 2009).…”
Section: Introductionmentioning
confidence: 99%